PREVALENCE AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF ESCHERICHIA COLI CAUSING URINARY TRACT INFECTION - ASATI RAKESH KUMAR; SADAWARTE KALPANA (International Journal of Pharma and Bio Sciences, 2013)
Urinary tract infection (UTI) is extremely common worldwide and numbers of patients are presenting to general practice and inpatient department. Gram negative bacteria are commonly involved in causing UTI. Escherichia coli is found to be the most common causative agent of UTI. Prudent and rational use of antimicrobial is possible by forming local, national and global wide antibiogram. This study is done to find out the prevalence and antimicrobial susceptibility pattern of E.coli causing urinary tract infection in tertiary care hospital, Bhopal. Total 1450 urine samples were collected and tested bacteriologically using standard procedures. Antimicrobial susceptibility testing was done by disk diffusion method described by Kirby-Bauer (1961). Culture positivity of urine samples was found to be 29 %.The most common pathogens were E.coli (62%) followed by Klebsiella ( 15.4 %), Enterobacter (6.9%), Pseudomonas (5.7%), Staphylococci aureus (5.7%) and others (4.3%). E.coli was found to be most sensitive to imipenem followed by polymyxin-B, nitrofurantoin, gatifloxacin, colistin, doxycycline, amikacin and Gentamycin.